Model Granuloma Tuberculosis In Vitro Sebagai Deteksi Awal Tingkat Keparahan Penyakit Tuberkulosis - Imam Agus Faizal (Jurnal Analis Medika Biosains (JAMBS), 2020)
Mycobacterium tuberculosis is a cause of Tuberculosis in humans causing death and one of the infectious agents in humans in the world. It is estimated that there are 8.7 million new cases, 1.4 million deaths, and around 2 billion latent infections caused by Mtb. According to WHO in 2014, an estimated 9.6 million people transmitted active TB disease, of which 1.5 million died and the burden of TB was heterogeneously distributed in various regions of the world. This type of research is a pure experiment with in vitro methods of making granuloma TB models that are similar to humans. The purpose of this study is to detect early the severity of tuberculosis. The results of the study that on the 1st day granuloma has not formed because the structure of granuloma has not formed yet because blood immune cells in PBMC media containing lymphocyte and monocyte cells are not yet responding to Mtb infection. On day 2 the granuloma structure surrounding the Mtb bacteria has begun to form forming an aggregation. Day 3, many other cell types also occupy granulomas, such as neutrophils, dendritic cells, B and T cells, natural killer cells, fibroblasts and cells that secrete extracellular matrix components. Day 4 granulomas undergo granulation and the structure of the granuloma breaks and maximum damage aggregation occurs on the 5th day. when the host's immune system weakens, it is known that active Mtb residents prevent active Tb. Experimental evidence has revealed that the TNF-α factor plays a major role in host defense against Mtb in both active and chronic infection phases. The study of granuloma tuberculosis from the above explanation can be concluded that the severity of tuberculosis can be detected early with the in vitro observation method of granuloma in order to provide appropriate drug therapy even this research can be used as an initial stage of perfecting the vaccine in tuberculosis infection.